Photodynamic inactivation of four Candida species induced by photogem® - Dovigo, Lívia Nordi [UNESP]; Pavarina, Ana Claudia [UNESP]; Ribeiro, Daniela Garcia [UNESP]; Adriano, Cynthia Sanchez [UNESP]; Bagnato, Vanderlei Salvador (Sociedade Brasileira de Microbiologia, 2010)
This study evaluated the in vitro susceptibility of C. albicans, C. dubliniensis, C. tropicalis and C. krusei to photodynamic therapy (PDT) induced by Photogem® and light emitting diode (LED). Suspensions of each Candida strain were treated with three photosensitizer (PS) concentrations (10, 25 and 50 mg/L) and exposed to 18.0, 25.5 and 37.5 J/cm² LED light fluences (λ ~ 455 nm). Control suspensions were treated only with PS concentrations, only exposed to the LED light fluences or not exposed to LED light or PS. Sixteen experimental conditions were obtained and each condition was repeated three times. From each sample, serial dilutions were obtained and aliquots were plated on Sabouraud Dextrose Agar. After incubation of plates (37 ºC for 48 hours), colonies were counted (cfu/mL) and the data were statistically analyzed by ANOVA and the Tukey test (α=0.05). Complete killing of C. albicans was observed after 18.0 J/cm² in association with 50 mg/L of PS. C. dubliniensis were inactivated after 18.0 J/cm² using 25 mg/L of PS. The inactivation of C. tropicalis was observed after photosensitization with 25 mg/L and subsequent illumination at 25.5 J/cm². For C. krusei, none of the associations between PS and light resulted in complete killing of this species. PDT proved to be effective for the inactivation of C. albicans, C. dubliniensis and C. tropicalis. In addition, reduction in the viability of C. krusei was achieved with some of the PS and light associations.
Keywords: Photochemotherapy; Candida; Hematoporphyrin Derivative